Relationship of Employment, Education, & Family Support with Exclusive Breastfeeding on Babies Aged more than 6 Months in Lubuk Batang Baru - Yeni Hartati; Tuti Farida; Sri Handayani; Helni Anggraini (JURNAL KEBIDANAN, 2021)
The most important nutritional needs of infants 0-6 months is by giving breast milk, because its composition is in accordance with the amount of nutrients needed by babies. Exclusive breastfeeding for infants aged 0-6 months is beneficial for the baby's survival, growth, and development. Starting from 2018-2020, the coverage of infants receiving exclusive breastfeeding in Lubuk Batang Baru Village did not exceed the strategic plan target.This study aims to determine the relationship between education, work and family support with exclusive breastfeeding for infants aged more than 6 months in Lubuk Batang Baru Village in 2021.This study is a quantitative study with a cross sectional approach. The sample of this study was a total population of 40 respondents. Bivariate analysis used in this study is chi square.The results showed that there was a relationship between education (p value 0.027), work (p value 0.038) and family support (p value 0.002) with exclusive breastfeeding for infants aged more than 6 months in Lubuk Batang Baru Village in 2021.